North Korean Miracle: 30 Уears of Surviving Crisis and Isolation - A. N. Lankov (Международная аналитика)
The article examines those factors that allowed the Kim family regime to stay in power in extremely unfavorable environment. In political science literature, it is generally accepted that an authoritarian regime faces three major threats: an elite conspiracy/coup, a mass protest, a foreign invasion. The article demonstrates that in the case of the DPRK, which is a much poorer part of a divided country, the potential threat of mass popular protests might be higher than in many other authoritarian regimes. However, the autocrat and his entourage successfully counter this threat by exercising an unusually thorough policy of informational self-isolation, further reinforced by strict administrative control and police surveillance. On the other hand, the ever present threat of Seoul-led “uniﬁcation-by-absorption” strengthens the elites’ unity and reduces the likelihood of conspiracies. This is important since elite conspiracies and coups have constituted the major danger for post-1945 autocracies. North Korean elites understand that even a successful coup can eventually provoke the outbreak of popular discontent, followed by the collapse of North Korean statehood and German-style uniﬁcation under Seoul’s control. Under this scenario, conspiracy’s winners and losers will perish alike, with all members of the current elite having little chance to retain their power and privileges. Hence, the elite has reasons not to “rock the boat.” Finally, the threat of a foreign invasion (or foreign intervention into a domestic crisis) is successfully neutralized by the existence of a nuclear deterrent. Since the North Korean faces a grave existential threat which is created by the existence of the South, it is ready to sacriﬁce the economic development for the sake of political stability. Hence, the elite is willing to invest large resources into military programs and overlook the diﬃculties the self-isolation and other survival-oriented policies create for the economic development of the country.